Hypertensive disorders of pregnancy-pre-conception and inter-conception care - Mala, Y. M.; Aggarwal, Sakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Women with hypertensive disorders during pregnancy face short- term and long-term complications which can impact both maternal as well as neonatal health. It is still a leading cause of maternal mortality despite aggressive treatment methods available. In the present article, effort has been made to address the potential threats and how and when to take certain preventive steps to improve the overall health of the woman before and after conceiving. It focuses on prenatal counselling, goals, lifestyle modifications and anti-hypertensive treatment.